2017
DOI: 10.1002/cctc.201700144
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalysis of Redox‐Active Bis(imino)acenaphthene (BIAN) Iron Complexes

Abstract: Reactions of various substituted bis(imino)acenaphthenes (R‐BIANs) with FeCl2(thf)1.5 afforded the tetrahedral complexes (R‐BIAN)FeCl2 (2) from bulky α‐diimines and the octahedral complexes [Fe(R‐BIAN)3][FeCl4]2 (3) from less bulky ligands. The driving force for the formation of complexes 3 is the high ligand‐field stabilization of the low‐spin FeII center. The two sets of complexes exhibit distinct charge‐transfer band intensities and redox activities. (R‐BIAN)FeCl2 complexes showed reversible ligand‐centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 102 publications
0
46
0
Order By: Relevance
“…[13] BIANs have mainly been exploited in noble-metalc atalysis so far, [14] whereas applications to 3d metal catalysis have only been reportedv ery sporadically;s ystematic investigations are still in their infancy. [15]…”
Section: Introductionmentioning
confidence: 99%
“…[13] BIANs have mainly been exploited in noble-metalc atalysis so far, [14] whereas applications to 3d metal catalysis have only been reportedv ery sporadically;s ystematic investigations are still in their infancy. [15]…”
Section: Introductionmentioning
confidence: 99%
“…Wangelin and co-workers reported that addition of n -BuLi (3 equiv.) to dpp BIANFeCl 2 generated an anionic [Fe] species, which was found to be an active hydrogenation catalyst for alkenes [147]. Inspired by this report, we applied the same conditions successfully to the hydrosilylation of esters and found that a broad scope of the substrate could be amenable to this transformation.…”
Section: Iron-catalyzed Hydrosilylationmentioning
confidence: 92%
“…There are many examples of iron(II) complexes possessing SMM or SIM behavior [ 4 , 6 , 16 , 22 , 23 , 24 , 25 , 26 ], but very rare examples of metal complexes are known that demonstrate both pronounced redox activity and SIM behavior [ 5 ]. The combination of non-innocent ligands based on α-diimines [ 27 ] and a redox-active iron ion has led to complexes exhibiting spin-crossover phenomenon [ 28 , 29 ] and promising catalytic activity in hydrogenations of olefins [ 30 ], hydrosilylation of aldehydes or carbonyl compounds [ 31 , 32 , 33 ], polymerization of ethylene [ 34 ] and styrene [ 35 ], and water reduction [ 36 ]. Among the existing α-diimine iron dihalides, the most studied complexes are chlorides (over a hundred deposited structures in CCDC) and bromides (about two dozen structures), and much less is known about iodides [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%